On‐metal UHF‐RFID passive tags based on complementary split‐ring resonators. Issue 7 (10th May 2017) - Zuffanelli, Simone; Zamora, Gerard; Paredes, Ferran; Aguila, Pau; Martin, Ferran; Bonache, Jordi
Abstract : The use of complementary split‐ring resonators (CSRRs) as radiating elements in low‐profile on‐metal ultra‐high‐frequency radio‐frequency identification (UHF‐RFID) tags is explored in this study. First, the radiation properties of the edge‐coupled and the non‐bianisotropic (NB‐CSRR) versions of the CSRR are studied. The tag design strategy is then discussed in detail. On that basis, a compact ( λ 0 /7 ×  λ 0 /7) low‐profile (1.27mm) tag prototype based on the non‐bianisotropic version of the CSRR (NB‐CSRR) antenna is designed and manufactured to operate in the North‐American UHF‐RFID band. The experimental results validate the theoretical and simulated behaviour, and exhibit a maximum read range of 6.8m.